Parents' decision making and access to preventive healthcare for young children: Applying Andersen's Model - Alexander, K.; Brijnath, Bianca; Mazza, D. (Wiley-Blackwell Publishing Ltd., 2015)
Background and objective: Implementing preventive health care for young children provides the best chance of improving health and changing a child's life course. In Australia, despite government support for preventive health care, uptake of preventive services for young children is low. Using Andersen's behavioural model of health-care utilization, we aimed to understand how parents conceptualized their children's preventive health care and how this impacted on access to preventive health-care services. Design: Semi-structured telephone interviews conducted between May and July 2011. Setting and participants: Twenty-eight parents of children aged 3-5 years from three diverse socio-economic areas of Melbourne, Australia. Results: Thematic analysis showed parents' access to child preventive health care was determined by birth order of their child, cultural health beliefs, personal health practices, relationship with the health provider and the costs associated with health services. Parents with more than one child placed their own experience ahead of professional expertise, and their younger children were less likely to complete routine preventive health checks. Concerns around developmental delays required validation through family, friends and childcare organizations before presentation to health services.Conclusions: To improve child preventive health requires increased flexibility of services, strengthening of inter-professional relationships and enhancement of parents' knowledge about the importance of preventive health in early childhood. Policies that encourage continuity of care and remove point of service costs will further reduce barriers to preventive care for young children. Recent reforms in Australia's primary health care and the expansion of child preventive health checks into general practice present a timely opportunity for this to occur.